Management by Missions - Cardona, P. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Management by Missions is the idea of distributing the corporate mission to all levels of a company. The corporate mission is then made operational through objectives, which have no value in themselves, but are vital as a means to fulfil the mission. This new management philosophy ensures better performance in all levels of the organization.